Natural Deep Eutectic Solvents Enhanced Electro-Enzymatic Conversion of CO2 to Methanol - Zhang, Zhibo; Wang, Hui; Nie, Yi; Zhang, Xiangping; Ji, Xiaoyan (Frontiers in Chemistry, 2022)
Electro-enzymatic conversion of CO2 offers a promising solution for CO2 utilization, while the conversion rate and efficiency were undesirable. To address the challenge, four kinds of natural deep eutectic solvents (NDES) with desirable biocompatibility were developed for the first time and used as the electrolyte in the electro-enzymatic conversion of CO2. As a result, the SerGly-based solution presents high CO2 solubility and high electrocatalytic activity, compared to the conventional buffer. By applying SerGly in the electro-enzymatic conversion of CO2, the yield of the product (methanol) is two times higher than that in the Tris-HCl buffer (0.22 mM) and 16 times higher than the control reaction.